Harry Potter and the prisoner of Azkaban - Rowling, J. K. (New York : Bloomsbury, 1999)
During his third year at Hogwarts School for Witchcraft and Wizardry, Harry Potter must confront the devious and dangerous wizard responsible for his parents' deaths.
Sequel to: Harry Potter and the Chamber of Secrets.
Sequel: Harry Potter and the goblet of fire.
Keywords: Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction; Schools -- Juvenile fiction; Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; England -- Juvenile fiction; England -- Fiction